2020
DOI: 10.1002/lary.29229
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Long‐Term Nasal Obstruction Symptom Evaluation Score Stability Following Septoplasty With Inferior Turbinate Reduction

Abstract: Objectives/Hypothesis Determine the postoperative Nasal Obstruction Symptom Evaluation (NOSE) score stability between 1 and ≥6 months after septoplasty with inferior turbinate reduction (ITR). Education level and occupation were evaluated to determine their effects on NOSE score stability during the postoperative period. Study Design Retrospective case series. Methods This was a retrospective case series. Patients were included if they underwent septoplasty with ITR for nasal obstruction due to septal deviatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…The mean postoperative score reflected mild symptoms on NOSE score scale, although it remained higher than the mean score of the control group, suggesting that nasal septoplasty resulted in improved disease-specific quality of life. This finding is consistent with previous studies reporting significant reductions in NOSE scores and improvements in disease-specific quality of life after nasal septoplasty with or without turbinate reduction 10,16–19. Likewise, a recent study assessing the outcomes of nasal septoplasty in 51 patients using NOSE scores found significant improvements in nasal obstruction 3 and 7 months postoperatively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The mean postoperative score reflected mild symptoms on NOSE score scale, although it remained higher than the mean score of the control group, suggesting that nasal septoplasty resulted in improved disease-specific quality of life. This finding is consistent with previous studies reporting significant reductions in NOSE scores and improvements in disease-specific quality of life after nasal septoplasty with or without turbinate reduction 10,16–19. Likewise, a recent study assessing the outcomes of nasal septoplasty in 51 patients using NOSE scores found significant improvements in nasal obstruction 3 and 7 months postoperatively.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with previous studies reporting significant reductions in NOSE scores and improvements in disease-specific quality of life after nasal septoplasty with or without turbinate reduction. 10 , 16 19 Likewise, a recent study assessing the outcomes of nasal septoplasty in 51 patients using NOSE scores found significant improvements in nasal obstruction 3 and 7 months postoperatively. The mean preoperative and 3- and 7-month postoperative NOSE scores were 60.3±20.4, 32.9±16.8, and 39.6±33.2, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The responsiveness and stability of NOSE allow the surveillance of symptom change over time. The use of NOSE demonstrated significant reduction of nasal obstruction was achieved at 1 month following septoplasty and turbinate reduction with the status quo remains unchanged at 6 months ( Law et al, 2021 ). A reliable postoperative evaluation is necessary as burden of disease varies from patient to patient and identification of problematic cases allows individualized management ( Gerecci et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, our retrospective design was susceptible to significant loss to follow‐up, as was encountered in our study at later timepoints of 3 and 6 months. Law et al recently showed that nasal obstruction symptoms do not significantly change postoperatively between 1 and 6 months, 22 suggesting that ETD symptom improvement after surgery for nasal obstruction may also be sustained across these timepoints. It is possible that our study underestimates long‐term improvements in nasal obstruction and ETD symptoms through selection bias, as patient visits at later timepoints may have been less likely to continue if symptoms had resolved.…”
Section: Discussionmentioning
confidence: 99%